LEGAL MECHANISMS OF DEMILITARIZATION OF THE MINISTRY OF DEFENSE OF UKRAINE AS A MEANS OF DEFENSE REFORM AND AN ELEMENT OF SECURITY SECTOR REFORM - Sadowskyi, Markian (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: consideration and solution of problematic issues of demilitarization of the Ministry of Defense of Ukraine as a means of defense reform and, in general, as an element of security sector reform. Research methods: the use of general scientific and special legal methods of cognition allowed to solve the scientific problem of the demilitarization of the Ministry of Defense of Ukraine as a means of defense reform and an element of security sector reform in general. Results: the problematic issues of demilitarization of the Ministry of Defense are investigated, the necessity and directions of security sector reform are determined. Discussion: in modern challenges, the concept of demilitarization of the Ministry of Defense of Ukraine should be understood not as reducing the size of the Armed Forces of Ukraine or reducing the fleet of military equipment, but as a way to increase the economic efficiency of structural elements of the Ministry of Defense. At present, the Ministry of Defense of Ukraine is in a state of continuous reform, which is critical to ensure the defense capabilities of the Armed Forces of Ukraine and other governing bodies and their ability to protect the territorial integrity of the state, especially in Ukraine’s active phase of armed conflict. to note a certain steady movement of Ukraine in the direction of demilitarization of the Ministry of Defense of Ukraine, including in understanding of civilization of this department. As noted above, only such an approach will provide Ukraine with the best opportunities for defense reform as an element of security sector reform that does not meet the goals and objectives of such reform, including in the light of international concepts in this area, without proper demilitarization of the Ministry of Defense of Ukraine.